2015
DOI: 10.5958/0975-6906.2015.00068.1
|View full text |Cite
|
Sign up to set email alerts
|

Marker assisted pyramiding of major blast resistance genesPi9andPitain the genetic background of an elite Basmati rice variety, Pusa Basmati 1

Abstract: Basmati is a premium quality rice of India which is highly priced in the international market. Pusa Basmati 1, an elite Basmati rice variety is highly susceptible to rice blast caused by Magnaporthe oryzae. Therefore, pyramiding blast resistance genes is essential to effectively combat the blast disease and increase the durability of resistance genes. The blast resistance genes Pi9 and Pita have been earlier demonstrated to be effective in Basmati growing regions of the country. Therefore, in the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…Accessions with pyramided R genes, such as IR56, IR64, as well as the resistant cultivar Tetep, were efficient across sites. Earlier studies reported that resistance was enhanced by the pyramid Pi-b+Pi-kh in the cultivar MR219 [32], Pi-1+Pi-2 in Rongfeng B [32], Pi9+Pita in Pusa Basmati 1 [34], and pi21+ Pi35 in Koshihikari [34]. In Africa, the R gene pyramiding approach has not yet been used for improving blast resistance in susceptible rice varieties.…”
Section: In Addition To the Susceptible Checks Maratelli Co 39 And Imentioning
confidence: 99%
“…Accessions with pyramided R genes, such as IR56, IR64, as well as the resistant cultivar Tetep, were efficient across sites. Earlier studies reported that resistance was enhanced by the pyramid Pi-b+Pi-kh in the cultivar MR219 [32], Pi-1+Pi-2 in Rongfeng B [32], Pi9+Pita in Pusa Basmati 1 [34], and pi21+ Pi35 in Koshihikari [34]. In Africa, the R gene pyramiding approach has not yet been used for improving blast resistance in susceptible rice varieties.…”
Section: In Addition To the Susceptible Checks Maratelli Co 39 And Imentioning
confidence: 99%
“…(Telomorph Pyricularia oryzae Sacc), is one of the major destructive disease on rice. Also known as rice fever disease, it was reported in all the rice growing countries of the globe 16 – 18 and it infects panicles, culm and leaves of the rice plants, consequently reducing photosynthetic efficiency and yield of rice grain 19 , 20 and causes 40–70% loss of rice grain 21 , 22 . For management of blast disease, use of chemical pesticides is not considered as an ecologically sound approach and fortification of host plant was a highly reasonable method 22 .…”
Section: Introductionmentioning
confidence: 99%
“…For screening the presence of the Pib resistance allele, a functional dominant marker (NSb) was used that targets part of the Pib gene and clearly differentiates the Pib resistance and susceptible alleles (Kwon et al, 2008). The Pi9 gene was incorporated in elite basmati cultivar Pusa basmati 1 along with another resistance gene, Pita (Apurva et al, 2015), and this gene was also introgressed into restorer contrast with Pi9, although Xa21 was originally identified and isolated from wild (Das et al, 2012). The Pi9 resistance allele was also screened with a tightly linked dominant marker that is within 0.2 cM of the gene (Liu et al, 2002).…”
Section: Screening Of Diverse Rice Accessions For Rice Blast and Bb Dmentioning
confidence: 99%
“…These resistance genes are also used in many blast resistance breeding programs. The Pi9 gene was incorporated in elite basmati cultivar Pusa basmati 1 along with another resistance gene, Pita (Apurva et al, 2015), and this gene was also introgressed into restorer contrast with Pi9, although Xa21 was originally identified and isolated from wild Oryza species (O. longistaminata), marker analysis revealed the presence of the Xa21 resistance allele in various accessions of O. sativa (79 accessions [37.44%] of 211 accessions). Many recent studies reported that the alleles identified in wild species can be present in O. sativa species.…”
Section: Screening Of Diverse Rice Accessions For Rice Blast and Bb Dmentioning
confidence: 99%